Electrocardiographic findings in myotonic dystrophy. Issue 1 (January 1988) - Olofsson, B O; Forsberg, H; Andersson, S; Bjerle, P; Henriksson, A; Wedin, I
Abstract : Sixty five patients with myotonic dystrophy, from a defined population in northern Sweden with an extremely high prevalence of this disease, were examined by electrocardiography. The patients were subdivided into three groups according to the severity of the disease. Abnormal electrocardiograms were found in 6 (35%) patients with mild disease, 12 (50%) patients with moderate disease, and 23 (96%) patients with severe disease. First degree atrioventricular block and left anterior hemiblock were the most commonly encountered abnormalities in patients with mild and moderate disease, whereas atrial fibrillation and flutter, abnormal Q waves, and repolarisation abnormalities were more common in patients with severe disease. This study shows that the heart is often affected by myotonic dystrophy. These effects can be detected by electrocardiography in early and mild forms of the disease. The effect on the heart is progressive and clinically important atrial arrhythmias and electrocardiographic abnormalities which are useful in differential diagnosis are common in severe forms of the disease.